Development of Multimedia Based Futsal Game Set Piece Training Model for Middle School - Ilham Surya Fallo; Suharjana; Widiyanto (Technium Social Sciences Journal, 2024)
This study aims to develop a multimedia-based futsal game set piece training model for junior high school extracurricular teachers in Pontianak City. This type of research is Research and Development (R&D) using the ADDIE model. The subjects in this study were junior high school students in Pontianak City who became extracurricular participants. The research instrument used in this study was a questionnaire. Analysis of the data used is a quantitative descriptive analysis technique with percentages. The conclusions in this study are: The implementation of small group trials showed 1 athlete (8.33%) gave a good response and as many as 11 athletes (91.67%) gave a good response. The large group trial showed that as many as 1 athlete (4.17%) gave a good response and as many as 23 athletes (95.83%) gave a very good response, so it can be concluded that the development of multimedia based futsal game set piece training is feasible to use in as the development of futsal training for extracurricular Middle School students in Pontianak City.